Predation by young Cassis tuberosa (Mollusca: Gastropoda: Cassidae) on Lytechinus variegatus (Echinodermata: Echinoidea), under laboratory Conditions - Pequeno, Ana Paula Leite Cavalcante (2014)
PEQUENO, A. P. L. C.; MATTHEWS-CASCON, H. Predation by young Cassis tuberosa (Mollusca: Gastropoda: Cassidae) on Lytechinus variegatus (Echinodermata: Echinoidea), under laboratory Conditions. Arquivos de Ciências do Mar. Fortaleza, v. 43, n. 2, p. 55-58, 2010.